The Utilization of E-Puskesmas in Supporting Learning and Competency Development of Health Workers: A Study of the Perception of Usability, Convenience, Attitudes, User Intentions, and Actual Use at the Puskesmas in the Solor Region, East Flores Regency - Maria Febriana P. Werang; Yusaq Tomo Adrianto; Syarif Hidayatullah (Edumaspul: Jurnal Pendidikan, 2026)
Digital transformation in the healthcare sector is driving the use of health information systems as a means of improving service quality and developing the competencies of healthcare workers. One innovation implemented in primary healthcare facilities is E-Puskesmas, an electronic-based information system that supports the integrated management of patient data, healthcare services, and healthcare center administration. This study aims to analyze the use of E-Puskesmas in supporting the learning and competency development of healthcare workers through a study of perceived usefulness, perceived ease of use, user attitudes, user intentions, and actual use at healthcare centers in the Solor area of ​​East Flores Regency. The study used a quantitative approach with an explanatory survey design. Data were obtained by distributing questionnaires to healthcare workers who use E-Puskesmas in their daily service activities. Data analysis was conducted using the Technology Acceptance Model (TAM) approach with Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that perceived usefulness and perceived ease of use play a significant role in shaping healthcare workers' positive attitudes toward using E-Puskesmas. This positive attitude fosters user intentions to utilize the system continuously, which in turn increases actual use in healthcare services. The actual use of e-Puskesmas not only improves the effectiveness and efficiency of services but also contributes to improving digital literacy, information technology skills, and the professional competence of healthcare workers through workplace learning. This study concludes that e-Puskesmas plays a strategic role as a healthcare service medium and a learning and competency development tool for healthcare workers. Therefore, training support, strengthening digital literacy, and developing a system tailored to user needs are needed to optimize the benefits of e-Puskesmas in supporting the digital transformation of healthcare services. Abstract Digital transformation in the health sector encourages the use of health information systems as a means of improving service quality as well as developing the competence of health workers. One of the innovations applied to first-level health service facilities is E-Puskesmas, which is an electronic-based information system that supports the management of patient data, health services, and the administration of health centers in an integrated manner. This study aims to analyze the use of E-Puskesmas in supporting the learning and competency development of health workers through a study of the perception of usability, perception of ease of use, user attitude, user intention, and actual use in the Puskesmas in the Solor area, East Flores Regency. The study uses a quantitative approach with an explanatory survey design. Data was obtained through the distribution of questionnaires to health workers who use E-Puskesmas in daily service activities. Data analysis was carried out using the Technology Acceptance Model (TAM) approach with Structural Equation Modeling techniques based on Partial Least Squares (SEM-PLS). The results of the study show that the perception of usability and the perception of ease of use play an important role in shaping the positive attitude of health workers towards the use of E-Puskesmas. This positive attitude encourages the formation of users' intention to utilize the system in a sustainable manner which further has an impact on increasing actual use in health services. The actual use of E-Puskesmas not only increases the effectiveness and efficiency of services, but also contributes to improving digital literacy, information technology skills, and professional competence of health workers through the work-based learning process (workplace learning). This study concludes that E-Puskesmas has a strategic role as a medium for health services as well as a means of learning and developing competencies of health workers. Therefore, training support, strengthening digital literacy, and developing systems that suit user needs are needed to optimize the benefits of E-Puskesmas in supporting the digital transformation of health services.